Lingkungan Keluarga, Entreepreneurial Mindset, dan Media Sosial terhadap Niat Berwirausaha Generasi Z: Peran Mediasi Motivasi Berwirausaha di Pontianak - Lina LINA; Afni Eliana Saragaih (LPPM STIEM BONGAYA, 2026)
Entrepreneurship development plays an important role in promoting economic growth; however, the level of entrepreneurship in Indonesia remains relatively low. This study aims to analyze the influence of family environment, entrepreneurial mindset, and social media on the entrepreneurial intention of Generation Z in Pontianak, with entrepreneurial motivation as a mediating variable. A quantitative explanatory research design was employed using data from 168 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed with IBM SPSS Statistics including validity, reliability, classical assumption, multiple linear regression analysis, and mediation analysis using Hayes’ PROCESS Model 4 with the bootstrapping method. The findings indicate that entrepreneurial mindset, social media, and entrepreneurial motivation have a positive and significant effect on entrepreneurial intention, whereas the family environment has no significant direct effect. In addition, the family environment and entrepreneurial mindset positively and significantly influence entrepreneurial motivation, while social media has no significant effect. Mediation analysis indicates that entrepreneurial motivation mediates the effects of the family environment and entrepreneurial mindset on entrepreneurial intention but does not mediate the effect of social media. These findings highlight the importance of entrepreneurial motivation in explaining how internal and external factors shape Generation Z’s entrepreneurial intention.